2017
DOI: 10.1007/s10113-017-1239-9
|View full text |Cite
|
Sign up to set email alerts
|

Managing Mediterranean soil resources under global change: expected trends and mitigation strategies

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 72 publications
(52 reference statements)
0
23
0
Order By: Relevance
“…Furthermore, the recent advances in sensor science support the innovation potential by exploiting the multiple research and operational assets in soil spectroscopy domain to effectively monitor SOC stocks for accounting purposes [110]. By that means, the generally low SOC content could ultimately increase via the adoption of appropriate management practices [111].…”
Section: Future Of Soil Spectroscopy In Soc Estimationmentioning
confidence: 99%
“…Furthermore, the recent advances in sensor science support the innovation potential by exploiting the multiple research and operational assets in soil spectroscopy domain to effectively monitor SOC stocks for accounting purposes [110]. By that means, the generally low SOC content could ultimately increase via the adoption of appropriate management practices [111].…”
Section: Future Of Soil Spectroscopy In Soc Estimationmentioning
confidence: 99%
“…For example, when considering climate data, several analysis (Jones et al ., ; Gobin & Govers, ) clearly showed that the values of essential precipitation characteristics, such as total annual precipitation, that were derived from the databases available at the European scale for Italy can deviate considerably (>50%) from more accurate estimates based on locally available data. A systematic soil survey of the Mediterranean region obtained by using the most updated technology and scientific knowledge is still lacking for site‐specific adaptation for local mitigation strategies and should be a priority in the near future (Lagacherie et al ., in press). Indeed, the sparseness of the legacy soil data available in the current soil databases has hampered the capture of short‐term soil property variations within the complex patterns of Mediterranean soil.…”
Section: Main Challenges For the Future Of Mediterranean Soil Resourcesmentioning
confidence: 99%
“…The Mediterranean region has a very long history of intense cultivation (De Franchis & Ibanez, ; Roose, ) with a unique combination of relief, climate conditions, soil forming factors and parent materials (Yaalon, ). Consequently, Mediterranean soils are very different from the soils in other regions in the world (Lagacherie et al ., in press). Conservation and management of Mediterranean soil resources have strongly contributed to the spread of successive civilizations in the past.…”
Section: Introductionmentioning
confidence: 99%
“…Around the world, conventional agriculture requires soils tillage twice a year before cereals sowing to control weed and to prevent crust formation. However, these practices added to climate change and soils vulnerability engendered erosion [4], soil moisture loss and soil organic matter reduction [5]. Consequently, conservation agriculture appeared such an alternative to conventional agriculture.…”
Section: Introductionmentioning
confidence: 99%